State-of-the-art of small animal imaging with high-resolution SPECT - Nikolaus, S.; Wirrwar, A.; Antke, C.; Kley, K.; Müller, H.-W. (Nuklearmedizin - NuclearMedicine, 2005)
During the recent years, in vivo imaging of small animals using SPECT has become of growing relevance. Along with the development of dedicated high-resolution small animal SPECT cameras, an increasing number of conventional clinical scanners has been equipped with single or multipinhole collimators. This paper reviews the small animal tomographs, which are operating at present and compares their performance characteristics. Furthermore, we describe the in vivo imaging studies, which have been performed so far with the individual scanners and survey current approaches to optimize molecular imaging with small animal SPECT.
Keywords: Small animal SPECT; pinhole SPECT; molecular imaging